Afforestation in the Cold Desert of India - Kaul, R. N. (Indian Forester, 1965)
The paper summarise the environmental conditions of Ladakh region. In view of extreme shortage of fuelwood in the region and paucity of other commercial fuels intensification of afforestation in suitable localities has been emphasised. Afforestation techniques adopted, species used and results achieved have been reviewed. Suggestions for improving the present method of irrigating plantation, introducing exotic species for fuel and fodder and soil conservation measures have been made.